Feeding selectivity of Holothuria atra in different microhabitat in Panjang Island, Jepara (Java, Indonesia) - Retno Hartati; AMBARIYANTO AMBARIYANTO; WIDIANINGSIH WIDIANINGSIH; MUHAMMAD ZAINURI (Society for Indonesian Biodiversity, 2020)
Abstract. Hartati R, Zainuri M, Ambariyanto A, Widianingsih W. 2020. Feeding selectivity of Holothuria atra in different microhabitat in Panjang Island, Jepara (Java, Indonesia). Biodiversitas 21: 2233-2239. Particle selectivity by deposit feeder sea cucumber Holothuria atra was an important concept in its feeding ecology. This species utilized the organic matter that coated sediment and detrital particles as food. Thus, particle size, organic matter, and microalgal biomass had been proposed as variables food resources along which niche separation could occur in optimal foraging strategy. This study was conducted in five microhabitats of different coverage of seagrass bed (P1-P4) up to the rubble area (P5) over a tidally variable depth range of 0,5-5m in Panjang island, Jepara. Twenty samples of sea cucumber H. atra were taken from defined microhabitat, along with samples of sediment underneath the sea cucumber. Granulometry of the particles ingested by sea cucumbers, total organic matter, and microphytobenthic biomass (as chlorophyll-a) found throughout their digestive tract (alimentary canal) and in the sediments was analyzed. Comparison of the contents and the rates of organic matter assimilation of the digestive tract with those of the microhabitat sediment were carried out. The results showed that H. atra fed on sediment underneath their body and it was revealed that there were strong (?=0.833-0.876) to very strong (?=0.945) positive relationship between grain size in the sediment and in their alimentary canal which showed their feeding selectivity of the sediment. H. atra also found to have efficiency in feeding by taking advantage of the high TOM content and high abundance of microphytobenthic organisms (presented as chlorophyll-a) in their natural microhabitats.